2008
DOI: 10.1111/j.1365-294x.2008.03920.x
|View full text |Cite
|
Sign up to set email alerts
|

Group composition affects male reproductive partitioning in a cooperatively breeding cichlid

Abstract: Individuals within groups of cooperatively breeding species may partition reproduction, with the dominant pair often taking the largest share. The dominant's ability to reproductively control subordinates may depend on differences in competitive ability, due to, e.g. body size differences, but may also depend on the number of same-sex competitors inside the group. We tested experimentally whether subordinates reproduce more when these subordinates are large or when a second subordinate of the same sex need to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 61 publications
(89 reference statements)
2
62
0
Order By: Relevance
“…Keeping such affiliative ties might help to counteract any negative effects of low exploration activity on finding alternative groups (e.g. Bergmü ller et al 2005;Heg et al 2008b), for example, to improve their social position ('queuing', Stiver et al 2006), because peaceful interactions with neighbouring groups might facilitate dispersal to these groups (see also Stiver et al 2004Stiver et al , 2006Stiver et al , 2007Bergmü ller et al 2005;Fitzpatrick et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Keeping such affiliative ties might help to counteract any negative effects of low exploration activity on finding alternative groups (e.g. Bergmü ller et al 2005;Heg et al 2008b), for example, to improve their social position ('queuing', Stiver et al 2006), because peaceful interactions with neighbouring groups might facilitate dispersal to these groups (see also Stiver et al 2004Stiver et al , 2006Stiver et al , 2007Bergmü ller et al 2005;Fitzpatrick et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, we predicted that extra-pair maternity (EPM) would be low regardless of territory location or density, because females in this species can recognize and destroy competitor eggs [27]. Regarding within-group characteristics, we predicted that parentage loss would increase as group size and the number of same-sex subordinates increased [4,5] and that subordinates closer in size to the dominant would be more likely to reproduce [8]. Finally, we predicted that a larger size difference between the dominant male and female would allow the dominant male to exert more control over group dynamics, facilitating subordinate or neighbouring female reproduction and suppressing subordinate or neighbouring male reproduction [9].…”
Section: Introductionmentioning
confidence: 96%
“…Individuals within a group may also come into conflict when group members mate with neighbouring individuals, as the offspring of neighbours may parasitize the resources and parental care of current group members [3]. Both within-group factors, such as group size and composition, and between-group factors, such as the density and location of neighbouring groups, influence the ability of individuals to pursue reproduction within their group [4,5] as well as pursue reproductive opportunities with neighbouring individuals [6,7]. Therefore, it is difficult to understand variation in individual behaviour or reproductive success without exploring how both within-group and between-group social structure affect the quality and quantity of reproductive opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…This might make attempts to obtain direct fitness benefits via parentage more rewarding. In a few cooperatively breeding birds and mammals, subordinates participating in reproduction also increased their helping effort in the field [22], [29], [64], [65] and a laboratory study of N. pulcher revealed that female subordinates may increase alloparental care in response to their participation in reproduction [30], [38]. These data suggest that more generally, directs fitness benefits might be an important modifier of subordinate helping intensities in cooperative breeders.…”
Section: Discussionmentioning
confidence: 80%
“…By participating in reproduction, subordinates face a threat of eviction [35], which may be detrimental due to the high mortality risk outside of territories [36]. In the laboratory, male subordinates unrelated to the breeding pair were found to participate in reproduction [31], [35], [37], [38]. However, their reproductive role in nature was questioned because subordinates have smaller gonads than breeders [17].…”
Section: Introductionmentioning
confidence: 99%